Crosslinking of human plasma C-reactive protein to human serum albumin via disulfide bond oxidation - Jiang, Shuwen (Redox Biol, 2021)
Inter- and intra-molecular crosslinks can generate protein dysfunction, and are associated with protein aggregate accumulation in aged and diseased tissues. Crosslinks formed between multiple amino acid side chains can be reversible or irreversible. Disulfides formed either enzymatically, or as a result of oxidant-mediated reactions, are a major class of reversible crosslinks. Whilst these are commonly generated via oxidation of Cys thiol groups, they are also formed by ‘oxidant-mediated thiol-disulfide reactions’ via initial disulfide oxidation to a thiosulfinate or zwitterionic peroxide, and subsequent reaction with another thiol including those on other proteins. This generates new intermolecular protein-protein crosslinks. Here we demonstrate that photooxidation, or reaction with the biological oxidants HOCl and ONOOH, of the single disulfide present in the major human plasma inflammatory protein, C-reactive protein (CRP) can give rise to reversible disulfide bond formation with human serum albumin (HSA). This occurs in an oxidant dose-, or illumination-time-, dependent manner. These CRP-HSA crosslinks are formed both in isolated protein systems, and in fresh human plasma samples containing high, but not low, levels of CRP. The inter-protein crosslinks which involve Cys36 of CRP and Cys34 of HSA, have been detected by both immunoblotting and mass spectrometry (MS). The yield of protein-protein crosslinks depends on the nature and extent of oxidant exposure, and can be reversed by dithiothreitol and tris(2-carboxyethyl)phosphine hydrochloride. These data indicate that oxidation of disulfide bonds in proteins can be a source of novel inter-protein crosslinks, which may help rationalize the accumulation of crosslinked proteins in aged and diseased tissues.